2019
DOI: 10.1021/acs.orglett.9b00820
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Synthesis, Crystal Structures, and Photophysical Properties of [6]Cycloparaphenylene Tetracarboxylates

Abstract: The synthesis of C 2-symmetrical [6]­cycloparaphenylene (CPP) tetracarboxylates has been achieved via macrocyclization by the rhodium-catalyzed intermolecular stepwise cross-alkyne cyclotrimerization and subsequent reductive aromatization. The 1H NMR spectra of the thus-obtained C 2-symmetrical [6]­CPP-tetracarboxylates revealed that the rotation of unsubstituted benzene rings is slow at room temperature. These [6]­CPPs formed columnar packing structures, and their absorption maxima were significantly blue-shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Chemie energy of 3b (120.6 kcal mol À1 )w as significantly larger than those of [16]CPPL (102.7 kcal mol À1 ) [3d] and spiro [8,8]CPP (92.2 kcal mol À1 ). [3e] Thep hotophysical and chiroptical properties of CPEs in dichloromethane are shown in Figure 3a nd the data are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Chemie energy of 3b (120.6 kcal mol À1 )w as significantly larger than those of [16]CPPL (102.7 kcal mol À1 ) [3d] and spiro [8,8]CPP (92.2 kcal mol À1 ). [3e] Thep hotophysical and chiroptical properties of CPEs in dichloromethane are shown in Figure 3a nd the data are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Forschungsartikel energy of 3b (120.6 kcal mol À1 )w as significantly larger than those of [16]CPPL (102.7 kcal mol À1 ) [3d] and spiro [8,8]CPP (92.2 kcal mol À1 ). [3e] Thep hotophysical and chiroptical properties of CPEs in dichloromethane are shown in Figure 3a nd the data are summarized in Table 2.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Our research group reported the synthesis of [6]cycloparaphenylene [7] tetracarboxylates, [ 6]CPP-(CO 2 R) 4 ,b yt he rhodium-catalyzed [2+ +2+ +2] cycloaddition of U-shaped prearomatic diynes with dialkyl acetylenedicarboxylates followed by reductive aromatization (Figure 1b). [8,9] In this reaction, two ethynyl groups of the U-shaped prearomatic diynes are close to each other, and thus the desired 1:1crosscycloaddition with dialkyl acetylenedicarboxylates proceeded smoothly.B esides the 1 HNMR analysis revealed that all benzene rings of [6]CPP-(CO 2 R) 4 are non-rotatable due to large ring strain. Based on these results,w ea nticipated that the cross-coupling between biphenyl-linked diyne 1a and Ushaped prearomatic diiodoparaphenylene 2 followed by reductive aromatization would also proceed smoothly to give CPE 3a,p ossessing stable axial and helical chirality,a s ar esult of the restricted rotation around the biphenyl and CÀCCÀCa xes [10] due to large ring strain as with [6]CPP (Figure 1c).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…">2.The comprehension of the driving forces for the supramolecular packing and cohesive energies of these systems as a function of their size, [ 107 ] therefore opening a way to tune their supramolecular structure to access solid‐state CNT‐like structures via the adequate functionalization, [ 108–110 ] and the determination of the preferred charge‐transfer career paths [ 111,112 ] ; 3.The differences between pristine and substituted CPPs, [ 113–121 ] with emphasis on intra‐molecular donor‐acceptor compounds [ 122–124 ] displaying fluorescent and semiconducting properties upon specific functionalization [ 125 ] ; 4.The influence of structural units after changing phenylene by pyrenylene (i.e., CycloPYrelenes [CPYs]) or ever larger structural motifs [ 126–128 ] and its effect on the single‐molecule [ 129 ] and supramolecular properties [ 130 ] ; and finally …”
Section: Introductionmentioning
confidence: 99%